2014
DOI: 10.5539/ibr.v7n3p13
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Supply Chain Management Practices on Supply Chain Performance in Jordan: The Moderating Effect of Competitive Intensity

Abstract: The purpose of this study is to test the impact of supply chain management practices on supply chain performance in terms of supply chain efficiency and supply chain effectiveness. Additionally, we investigate the moderating effect of competitive intensity on the relationship between supply chain management practices and supply chain performance. Data for this research were collected from 104 manufacturing companies in Jordan. Hierarchical regressions were used to test the hypothesized relationships. The resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
84
4
20

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(113 citation statements)
references
References 56 publications
5
84
4
20
Order By: Relevance
“…There is general agreement in the literature that supplier collaboration and integration positively affect company's overall performance. Previous empirical studies confirmed such positive effect (e.g., Abdallah et al, 2014;Flynn et al, 2010). This result can be justified by at least three arguments.…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…There is general agreement in the literature that supplier collaboration and integration positively affect company's overall performance. Previous empirical studies confirmed such positive effect (e.g., Abdallah et al, 2014;Flynn et al, 2010). This result can be justified by at least three arguments.…”
Section: Discussionsupporting
confidence: 54%
“…Secondly, customer collaboration in most studies was viewed as a general construct that implicitly or explicitly included all customers, regardless of their relative importance to the organization. This situation may explain the failure of several studies to find a significant relationship between customer collaboration and performance dimensions (e.g., Abdallah et al, 2014, Sundram et al, 2011Flynn et al, 2010). While collaborations with suppliers and customers are widely recognized as beneficial SC aspects, less attention was given to supplier and lead user collaboration in new product development, which will be discussed in the following sections.…”
Section: Sc Collaborationmentioning
confidence: 90%
See 1 more Smart Citation
“…This rate is relatively high compared with other empirical studies conducted in Jordan. For example, [111] got a response rate of 57.7%, [32] showed a response rate of 52%, and [112] received a response rate of 59.5%.…”
Section: Surveymentioning
confidence: 99%
“…Pertama, menurut literatur manajemen rantai pasokan, penelitian tentang praktik-praktik rantai pasokan masih menggunakan berbagai konstruk yang berbeda-beda dan memberikan temuan yang belum konklusif. Hal tersebut membuat para peneliti menjadi kebingungan (Abdallah et al, 2014). Setidaknya, terdapat lima konstruk atau dimensi praktik-praktik rantai pasokan yang sering digunakan dalam berbagai penelitian (e.g.…”
unclassified